2016
DOI: 10.1158/1541-7786.mcr-15-0450
|View full text |Cite
|
Sign up to set email alerts
|

Kinase-Dependent and -Independent Roles for PTK6 in Colon Cancer

Abstract: Disruption of the gene encoding Protein Tyrosine Kinase 6 (Ptk6) delayed differentiation and increased growth in the mouse intestine. However, Ptk6 null mice were also resistant to azoxymethane-induced colon tumorigenesis. To further explore functions of PTK6 in colon cancer, expression of epithelial and mesenchymal markers, as well as proliferation, migration, and xenograft tumor growth were examined in human colon tumor cell lines with knockdown or overexpression of PTK6. PTK6 protein, transcript, and activa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 46 publications
(71 reference statements)
2
24
2
Order By: Relevance
“…Interestingly, PTK6 may play a tissue-dependent role in regulating EMT. In contrast to our results with breast epithelial cells and TNBC cells, Mathur and colleagues recently reported that PTK6 promotes the epithelial phenotype in the context of a colon cancer cell line, and PTK6 shRNA expression increased migration, suppressed E-cadherin expression and increased mesenchymal marker expression (49). These seemingly contradictory roles of PTK6 in EMT may be due to tissue-specific contexts, as PTK6 specifically plays a role in the differentiation of colonic epithelial cells (50).…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, PTK6 may play a tissue-dependent role in regulating EMT. In contrast to our results with breast epithelial cells and TNBC cells, Mathur and colleagues recently reported that PTK6 promotes the epithelial phenotype in the context of a colon cancer cell line, and PTK6 shRNA expression increased migration, suppressed E-cadherin expression and increased mesenchymal marker expression (49). These seemingly contradictory roles of PTK6 in EMT may be due to tissue-specific contexts, as PTK6 specifically plays a role in the differentiation of colonic epithelial cells (50).…”
Section: Discussioncontrasting
confidence: 99%
“…The inhibitory role of PTK6 in Wnt signalling raises the idea that the kinase may be downregulated in colorectal carcinogenesis. Indeed, a recent study showed that the level of PTK6 expression was decreased in clinically isolated human colorectal cancers 45 .…”
Section: Discussionmentioning
confidence: 99%
“…PTK6 is a poorly characterized tyrosine kinase, which is amplified or overexpressed in 16% of CRC patients. PTK6 can stimulate CRC cell survival and oncogenic signaling in a kinase dependent manner, but suppresses epithelial-to-mesenchymal transition in a kinase independent fashion 39 . PTK6 rewiring mostly decreased interactions with the CCT chaperonin complex in mtKRAS Hi cells, whereas the interaction with metastasis associated 1 family member 2 (MTA2) was increased (Supplementary Fig.…”
Section: Sh2d3c Prkd1mentioning
confidence: 99%